Feeding Volatiles of Larval Sparganothis pilleriana (Lepidoptera: Tortricidae) Attract Heterospecific Adults of the European Grapevine Moth. Issue 6 (22nd September 2021) - El-Sayed, Ashraf M; Ganji, Suresh; Unelius, C Rikard; Gemeno, César; Ammagarahalli, Byrappa; Butler, Ruth C; Hoffmann, Christoph
Abstract: Plants release volatiles in response to caterpillar feeding. These herbivore-induced plant volatiles (HIPVs) attract natural enemies of the herbivores and repel or attract conspecific adult herbivores in a tri-trophic interaction which has been considered to be an indirect plant defense against herbivores. Recently, we demonstrated the attraction of male and female European grapevine moth, Lobesia botrana (Denis & Schiffermüller) (Lepidoptera: Tortricidae) to a blend of phenylacetonitrile and acetic acid, two compounds identified as HIPVs in heterospecific apple-leafroller interactions. The ecological basis of our findings is not clearly understood. Thus, this work was undertaken to investigate HIPVs in the grapevine-leafroller interaction and study the response of heterospecific adults L. botrana, to these volatiles. We collected headspace volatiles emitted from uninfested grapevines and grapevines infested with larvae of a generalist herbivore, the grapevine leafroller moth, Sparganothis pilleriana (Denis & Schiffermüller), and analyzed them using gas chromatography/mass spectrometry. Infested grape leaves released three compounds (phenylacetonitrile, indole, and 2-phenylethanol) not found from uninfested leaves. Nine different blends, comprising a full factorial set of the three compounds with each blend containing acetic acid, were tested in a field-cage trial. Only lures containing phenylacetonitrile caused a significant increase in trap catches compared to the other lures and blank traps. Electroantennographic tests show that L. botrana can detect the compounds. The results confirm our hypothesis that phenylacetonitrile is released during grapevines infestation with herbivores, and attracts adult L. botrana . Graphical Abstract: